Cantwell, Theresa Squires. Black and white photograph of two women holding babies from Theresa Squires Cantwell's personal photograph collection. - Barrett, Terra
Left to right: Gertrude Squires holding Theresa Squires, and Eileen Squires holding holding Eileen Squires.